The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1177/000992289303200503
|View full text |Cite
|
Sign up to set email alerts
|

Rectal-Axillary Temperature Difference in Febrile and Afebrile Infants and Children

Abstract: The rectal-axillary temperature difference (R-A) was measured in the morning, at midday, and in the afternoon on 1,519 occasions in 1,149 children from birth to 5 years old. Of these, 302 children were febrile (rectal temperature > or = 38 degrees C) and 847 were afebrile. A wide range in R-A was found for each individual in both groups. The magnitude of this difference was not associated with sex or age. In febrile children, the R-A was significantly greater (P < .0001) at the apparent onset of fever (1.04 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1995
1995
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Our findings are in agreement with those of Vernon, et al [15] and Scolnik, et al [14], but different from those of Leary et al [13]. These differences may be attributed to the fact that in Leary's study, all outcome measurements were based on axillary temperatures, the reliability of which is uncertain [16]. …”
Section: Discussionsupporting
confidence: 85%
“…Our findings are in agreement with those of Vernon, et al [15] and Scolnik, et al [14], but different from those of Leary et al [13]. These differences may be attributed to the fact that in Leary's study, all outcome measurements were based on axillary temperatures, the reliability of which is uncertain [16]. …”
Section: Discussionsupporting
confidence: 85%
“…However, differences between axillary and rectal temperatures may be more important during the variations of body temperature. 34,35 This may also contribute to the observation of lower temperature in adults. Finally, the most striking observation was the very short duration of a high proportion of fever episodes during malaria attacks regardless of the age of the patients.…”
Section: Discussionmentioning
confidence: 93%
“…21 However, they employed axillary temperature, which is not reliable. 24 In a study conducted by Keinanen et al, oral acetaminophen was reported to be more effective and its effect was observed faster. 25 Nonetheless, this study was not randomized and a low dose of 10 mg/kg acetaminophen was administered.…”
Section: Discussionmentioning
confidence: 98%